Vegetation influences soil properties along riparian zones of the Beijiang River in Southern China - Qinghe Zhao; Shengyan Ding; Qian Liu; Shuoqian Wang; Yaru Jing; Mengwen Lu (PeerJ, 2020)
Riparian soils and vegetation are important factors influencing the biodiversity and biogeochemical processes of river ecosystems. Riparian soils and vegetation form the foundation for multiple ecosystem services provided by river ecosystems. However, it remains poorly understood how riparian soils and vegetation interact with one another to maintain these services. In this study, we sampled four common types of riparian vegetation associated with the Beijiang River in South China. These included forestland, bamboo forest, mixed forest, and grassland ecosystems. Specifically, we analyzed the spatial distribution of riparian soils and their response to environmental factors (i.e., coverage and height of trees, shrubs and grass, distance to river, and altitude). Our results indicate that soil properties in riparian zones were affected significantly by vegetation type. In particular, clay content, soil organic carbon, and nitrate nitrogen content were significantly correlated with vegetation type. In contrast, changes in soil total nitrogen, total phosphorus, and available phosphorus content were not associated with vegetation type. Moreover, soil physical and chemical properties interacted with one an other, as well as with vegetation characteristics. This was indicated by the significant correlation observed between soil organic carbon, total nitrogen, total phosphorus, and soil texture, with structural characteristics of the four vegetation types. We also found that height and cover of trees and shrubs were significantly correlated with soil chemical properties. However, the effects of topographic variables such as altitude and distance to river were not significant. Results from this study can thus provide a basis for the ecological restoration and land management of degraded iparian zones.